2015
DOI: 10.2478/jomb-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Carnitine Supplementation on Circulating C-Reactive Protein Levels: A Systematic Review and Meta-Analysis / Uticaj Suplementacije L-Karnitinom Na Nivoe C-Reaktivnog Proteina U Cirkulaciji: Sistematski Pregled I Metaanaliza

Abstract: SummaryBackgroundC-reactive protein (CRP) has been proposed as a risk marker and risk factor of cardiovascular disease. There have been a number of clinical reports suggesting that supplementation with L-carnitine can modulate systemic inflammation and lower circulating CRP concentrations, but the results have not been consistent.MethodsA comprehensive literature search in Medline, Scopus and Cochrane Central Register of Controlled Trials was performed in December 2012 to identify clinical trials investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
3
14
1
Order By: Relevance
“…Furthermore, a study on hemodialysis patients with hyper lipo-proteinemia reported that 1000 mg/d of oral L-carnitine could reduce in ammation but didn't affect oxidative stress [33]. Moreover, a meta-analysis con rmed that L-carnitine can reduce CRP [13]. In comparison with the current research, CRP reduction in this study may be due to injection of L-carnitine and longer duration of the study.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Furthermore, a study on hemodialysis patients with hyper lipo-proteinemia reported that 1000 mg/d of oral L-carnitine could reduce in ammation but didn't affect oxidative stress [33]. Moreover, a meta-analysis con rmed that L-carnitine can reduce CRP [13]. In comparison with the current research, CRP reduction in this study may be due to injection of L-carnitine and longer duration of the study.…”
Section: Discussioncontrasting
confidence: 43%
“…Earlier studies showed that L-carnitine can signi cantly reduce CRP and MDA in coronary [29,30] and hemodialysis patients [31]. Meta-analysis also showed that L-carnitine supplementation signi cantly reduced the levels of CRP [13], cholesterol and lowdensity lipoprotein cholesterol (LDL-C) in diabetic patients [14]. Recent study also reported that 750 mg of Lcarnitine supplementation had no effect on serum lipid pro le and hs-CRP in women with KOA [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the deficiency in L-Carnitine may be associated with a syndrome of progressive skeletal myopathy and cardiomyopathy. 17,18 Thus, L-Carnitine may be useful in patients with toxic injuries, particularly in oncology profile patients.…”
Section: Discussionmentioning
confidence: 99%
“…LC has been reported to increase antioxidant enzyme activity and to regulate fatty acid and glucose metabolism for energy balance (Calvani, Reda, & Arrigoni‐Martelli, ). Prior studies have suggested that LC supplementation has beneficial effects on metabolic syndrome components such as hyperlipidemia (Askarpour et al, ), hypertension (Askarpour et al, ), insulin resistance (Xu et al, ), and oxidative stress and inflammation (Mohammadi et al, ; Nazary‐vannani et al, ; Sahebkar, ).…”
Section: Introductionmentioning
confidence: 99%